Technical Note: Mean Lead‐Time as a Real‐Time Key Performance Indicator. (23rd May 2020) - Niemi, Tapio; Gallay, Olivier; Hameri, Ari‐Pekka
ABSTRACT: Measuring the average time that a process takes from start to finish, using observation time windows (OTWs) of different length, is required for numerous operational monitoring and control processes. We refer to this measure as the Mean Lead‐Time (MLT). This study is based on the fact that computing the MLT in an operational context is often misleading for two reasons: (1) the computed value directly depends on the length of the used OTW; and (2) some jobs are usually still running at the end of the OTW, and thus their final lead‐time is not known yet. To overcome these issues, we revisit the definition of the MLT as well as the way to measure it. We develop a method to take these two aspects into account and apply this method to four real‐life cases in different business contexts. Using these practical cases, we show that the proposed methodology makes it possible to compute a standardized measure of the MLT, allowing for a meaningful comparison when different OTW lengths are considered. These new results open the door for an efficient use of the MLT as a commensurable performance indicator and allow near real‐time monitoring and comparison across different process steps, departments, and factories.